Shakespeare et les amours de Diane : Endymion, Hippolyte et Adonis - Agnès Lafont (Itinéraires)
Shakespearean recreations of masculine beauty combine two mythological references, Adonis in Venus and Adonis (1594) and Endymion in The Merchant of Venice (1596), with the myth of Diana, using classical tradition and humanist mythographies. A new canon of masculine beauty is thus defined by this mythological network of references. Hippolytus, another of Diana’s loved ones, appears in a subterraneous manner to enhance the interaction between Diana as the moon goddess and as the huntress. The readings of these fabulae celebrates a new masculine beauty, ambiguous, and much to the audience’s taste in the 1590s.